Pembangunan Video Animasi 3 Dimensi Tentang Bahaya Narkoba, HIV / Aids Dan Seks Bebas - Frestika Cahyo Hakim .; Indah Uly Wardati . (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
ABSTRACT Currently drug problems, HIV / AIDS and promiscuity often discussed. Many cases thatoccur due to drugs, HIV / AIDS and free sex. With the drug problems, HIV / AIDS and free sexhappens in Pacitan, many speakers giving advice on the dangers of drugs, HIV / AIDS and free sex inorder to later drug problems, HIV / AIDS and free sex did not increase much. Then be made to themedia information in the form of 3-D animated video about the dangers of drugs, HIV / AIDS and freesex. The purpose of this research is the creation of three-dimensional animated video about thedangers of drugs, HIV / AIDS and free sex that does not fall into that issue and assist communicatorsin providing materials about the dangers of drugs, HIV / AIDS and promiscuity.The benefit of this study is as a medium of information about the dangers of drugs, HIV / AIDS andfree sex. Teens can avoid drugs, HIV / AIDS and free sex and can choose a healthy society, free fromdrugs, HIV / AIDS and free sex.Methods band is used in the manufacture of 3-D video animation writeruses library methods, observation and interviews. Designing using 3Ds Max 2010, Sony Vegas Pro10, Adobe Photoshop CS3 and Corel Draw X4.Keywords: Drugs, HIV AIDS and Free SexABSTRAKSI Saat ini masalah narkoba, HIV / AIDS dan seks bebas sering sekali dibicarakan. Banyakkasus yang terjadi akibat narkoba, HIV / AIDS dan seks bebas. Dengan adanya masalah narkoba, HIV/ AIDS dan seks bebas yang terjadi di Pacitan, banyak narasumber memberi nasehat tentang bahayanarkoba, HIV / AIDS dan seks bebas agar nantinya masalah narkoba, HIV / AIDS dan seks bebastidak bertambah banyak. Maka dibuatlah media informasi berupa video animasi 3 dimensi tentangbahaya narkoba, HIV / AIDS dan seks bebas.Tujuan penelitian ini adalah terciptanya video animasi 3 dimensi tentang bahaya narkoba, HIV / AIDSdan seks bebas agar remaja tidak terjerumus dalam masalah itu dan membantu para komunikatordalam memberikan materi tentang bahaya narkoba, HIV / AIDS dan seks bebas. Manfaat daripenelitian ini adalah sebagai media informasi tentang bahaya narkoba, HIV / AIDS dan seks bebas.Remaja bisa menghindari narkoba, HIV / AIDS dan seks bebas serta bisa memilih pergaulan yangsehat, bebas dari narkoba, HIV / AIDS dan seks bebas.Metode yang di gunakan dalam pembuatan video animasi 3 dimensi penulis menggunakan metodepustaka, observasi dan wawancara. Perancangan menggunakan 3Ds Max 2010, Sony Vegas Pro 10,Adobe Photoshop cs3 dan Corel Draw X4.Kata Kunci : Narkoba, HIV AIDS dan Seks Bebas